2008
DOI: 10.1002/da.20337
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of duloxetine in the treatment of generalized anxiety disorder in patients with clinically significant pain symptoms

Abstract: Anxiety disorders often are accompanied by painful physical symptoms. This report assessed the effectiveness of duloxetine in improving anxiety symptoms, pain severity, and patient functioning in adults diagnosed with generalized anxiety disorder (GAD), who presented with clinically significant pain symptoms. Data were pooled from two multicenter, randomized, double-blind, placebo-controlled clinical studies evaluating the efficacy of duloxetine 60-120 mg once daily compared with placebo in the treatment of GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
5
17
0
2
Order By: Relevance
“…These analyses also showed that among both relapsers and nonrelapsers, duloxetine-treated patients tended to have lower pain severity than placebo-treated patients, particularly among nonrelapsers. Our finding that relapsers tended to have a better response to duloxetine than to placebo on most pain scales supports a previous finding that suggested that duloxetine's effect on pain is at least in part independent of changes in anxiety symptoms (Russell, Weisberg et al, 2008). These findings, combined with our observation that some GAD nonrelapsers experienced worsening of their pain symptoms, especially when switched to placebo, suggest that painful physical symptoms may be somewhat independent of other core anxiety symptoms in GAD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These analyses also showed that among both relapsers and nonrelapsers, duloxetine-treated patients tended to have lower pain severity than placebo-treated patients, particularly among nonrelapsers. Our finding that relapsers tended to have a better response to duloxetine than to placebo on most pain scales supports a previous finding that suggested that duloxetine's effect on pain is at least in part independent of changes in anxiety symptoms (Russell, Weisberg et al, 2008). These findings, combined with our observation that some GAD nonrelapsers experienced worsening of their pain symptoms, especially when switched to placebo, suggest that painful physical symptoms may be somewhat independent of other core anxiety symptoms in GAD.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, at study entry, the mean VAS scores for overall pain and time in pain exceeded 30 and were therefore indicative of clinically significant pain (Collins, Moore, McQuay, 1997). This study differs from previous analyses in that patients were not selected on the basis of pain at baseline Russell, Weisberg et al, 2008); the findings in this large general clinical population of patients with GAD suggest that painful physical symptoms are common in GAD and are relevant as a part of this disease state.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…To date, dual-action medications that enhance serotonergic and noradrenergic neurotransmission simultaneously have been shown to improve both pain and symptoms of depression (Detke et al, 2002) or anxiety (Russell JM, 2007). However, use of these agents in BD is problematic because of the significant risk of inducing mania (Ghaemi et al, 2003) There is also evidence supporting the use of non-pharmacologic interventions targeting anxiety or depression as well as pain (Christie et al, 2007; Otto et al, 2007; Rooks et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While there are few data available, duloxetine has demonstrated efficacy for both GAD and pain symptoms in RCTs [1435-1437]. TCAs, and to a lesser extent SSRIs, have been shown to reduce headache attacks in patients with migraine [1438], and provide moderate relief of neuropathic pain [1439].…”
Section: Anxiety With Comorbid Conditionsmentioning
confidence: 99%